Pump laser induced photodarkening in ZrO2-doped Yb:Y2O3 laser ceramics - Wang, Jun (2021)
5 at.% Yb:Y2O3 transparent ceramics were fabricated using vacuum sintering plus HIP. The ceramics doped with 1 at.% ZrO2 as the sintering additive were densified at 1700 °C in vacuum followed by HIPing at 1775 °C, while those without sintering additives were densified at 1520 °C in vacuum followed by HIPing at 1450 °C. After sintering, both ceramics had relatively high in-line transmittance. However, during laser experiments, the ZrO2-doped Yb:Y2O3 (Zr-YbY) ceramics were photodarkened when irradiated by 940 nm pump light. The discoloration might be attributed to the formation of Zr3+ color centers during lasing. In contrast, no photodarkening effect was detected in the pure Yb:Y2O3 ceramics without sintering additives (P-YbY). The P-YbY ceramics exhibited much higher lasing efficiency (17%) than the Zr-YbY ceramics (9%). To our best knowledge, it is the first time that the photodarkening effect was detected in rare-earth doped sesquioxide laser ceramics.